Roadmap for alleviating the manifestations of ageing in the cardiovascular system - Liberale, Luca; Tual-Chalot, Simon; Sedej, Simon; Ministrini, Stefano; Georgiopoulos, Georgios; Grunewald, Myriam; Bäck, Magnus; Bochaton-Piallat, Marie-Luce; Boon, Reinier A.; Ramos, Gustavo Campos; de Winther, Menno P. J.; Drosatos, Konstantinos; et al. (Nature reviews. Cardiology, 2025)
Ageing of the cardiovascular system is associated with frailty and various life-threatening diseases. As global populations grow older, age-related conditions increasingly determine healthspan and lifespan. The circulatory system not only supplies nutrients and oxygen to all tissues of the human body and removes by-products but also builds the largest interorgan communication network, thereby serving as a gatekeeper for healthy ageing. Therefore, elucidating organ-specific and cell-specific ageing mechanisms that compromise circulatory system functions could have the potential to prevent or ameliorate age-related cardiovascular diseases. In support of this concept, emerging evidence suggests that targeting the circulatory system might restore organ function. In this Roadmap, we delve into the organ-specific and cell-specific mechanisms that underlie ageing-related changes in the cardiovascular system. We raise unanswered questions regarding the optimal design of clinical trials, in which markers of biological ageing in humans could be assessed. We provide guidance for the development of gerotherapeutics, which will rely on the technological progress of the diagnostic toolbox to measure residual risk in elderly individuals. A major challenge in the quest to discover interventions that delay age-related conditions in humans is to identify molecular switches that can delay the onset of ageing changes. To overcome this roadblock, future clinical trials need to provide evidence that gerotherapeutics directly affect one or several hallmarks of ageing in such a manner as to delay, prevent, alleviate or treat age-associated dysfunction and diseases.
Online veröffentlicht: 19. Februar 2025
Gesehen am 15.07.2025